Self-care knowledge, attitude and associated factors among outpatients with diabetes mellitus in Arsi Zone, Southeast Ethiopia. - Rahel Nega Kassa; Hana Abera Hailemariam; Mekdes Hailegebreal Habte; Altayework Mekonnen Gebresillassie (Public Library of Science (PLoS), 2021)
Introduction Diabetes mellitus is a chronic illness that requires continuing medical care and ongoing patient self-management, education and support to prevent acute complications and to reduce the risk of long-term complications. Therefore, this study aims to assess the self-care knowledge, attitude and associated factors among outpatients with diabetes mellitus in Arsi Zone, Southeast Ethiopia. Materials and methods A cross sectional study was employed in Arsi Zone, Southeast Ethiopia from April to June 2017 among 290 patients with diabetes mellitus. Structured questionnaire was employed through face to face interview. Bivariate and multivariate regression was done and a statistical significance was declared at p value < 0.05. Results Among 290 respondents, 64.8% and 27.6% of them had good knowledge and good attitude towards self-care in this study respectively. Being married (AOR: 3.41, 95% CI: 1.480-8.095), being employed in occupation (AOR: 5.8, 95% CI: 2.26-14.67) and living in higher socioeconomic status (AOR: 2.0, 95% CI: 1.096-3.322) are the independent factors associated to good knowledge of respondents towards self-care whereas living in lower socioeconomic status(AOR: 0.478, 95% CI: 0.262-0.874), having informal education (AOR: 4.002, 95% CI: 1.941-8.254), not having family history of diabetes mellitus (AOR: 0.422, 95% CI: 0.222-0.803) and having short duration of diagnosis (AOR: 3.209, 95% CI: 1.537-6.779) were significantly associated factors to have poor attitude towards self-care. Conclusion Majority of the study participants had good knowledge towards diabetes self-care practice while a significant number of the participants had unfavorable attitude towards diabetes self-care. Being married, being employed and living in higher socioeconomic status were the determinant factors of knowledge towards the diabetes self-care practice while having informal education and having short duration of diagnosis were the significant factors associated to the unfavorable attitude towards diabetes self-care practice. Therefore, efforts should be made on enhancing patients' socioeconomic status and equipping with diabetic self-care centered health information particularly for those patients with short duration of diagnosis.